Synthesis of Wax Esters by Lipase-catalyzed Esterification with Immobilized Lipase from Candida sp. 99-125 - 邓利 王晓静 聂开立 王芳 刘军峰 王璞 谭天伟 (Chinese journal of chemical engineering, 2011)
Wax esters were synthesized in a solvent free system catalyzed by immobilized lipase from Candida sp. 99-125, with oleic acid and cetyl alcohol. The effects of substrate molar ratio, lipase dosage and water removal were investigated in a 50 ml flask incubated in a thermostatic cultivation cabinet. The optimized conditions were： temperature 40 ℃, shaking at 170 r·min-1, acid/alcohol molar ratio 1：0.9, lipase dosage in 10% （by mass） of oleic acid, and open reaction for water removal. As a result, the conversion rate reached 98% for reaction of 8 h. The volume of reactor was scaled up to 1 L three-neck flask. The optimized parameters were： 200 r·min-1 agitation speed, 2.5% （by mass） lipase dosage, others were the same as the parameters described above. The conversion rate reached 95% for reaction of 24 h. The lipase retained 46% conversion rate after reuse for 6, 7 batches. The products were purified by removing remained cetyl alcohol and fatty acids with ethanol and saturated sodium carbonate so-lution, respectively. The purity of the wax ester, cetyl oleate, was 96%. The physical and chemical properties of cetyl oleate were tested and compared with those of jojoba oil. The results show that the product cetyl oleate has great potential to use as the substitute of natural jojoba oil.